PERSEPSI MAHASISWA CALON GURU TERHADAP PEMAHAMAN LITERASI LINGKUNGAN - ira (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2022)
Future generations need to be provided with provisions and insights into the environment so that an environmentally literate generation is formed. Likewise, prospective teacher students at the Faculty of Teacher Training and Education, Universitas Ahmad Dahlan need to gain insight related to environmental literacy. The purpose of this study is to determine the perception of FKIP UAD students towards understanding environmental literacy and for the level of understanding of student environmental literacy. This research is a survey research with questionnaire techniques and instruments used to collect data using questionnaires. Data analysis techniques use quantitative descriptive analysis. The population in this study was all FKIP UAD students class of 2018, the sample used was 219 students with random sampling techniques. The results showed that the perception of FKIP UAD students towards understanding environmental literacy was included in the sufficient category, student perception of understanding environmental literacy included 4 aspects, namely competence towards the environment, knowledge of the environment, attitude towards the environment, and behavior and responsibility towards the environment Key words: perception, future teacher, literacy, environment